Análise energética e fluidodinâmica de trocadores de calor - Bavia Filho, Otávio Celso (2015)
This paper presents a proposal for energy analysis of thermal efficiency for a shell and tube heat exchanger. The analyzes were based on an oil cooler of a compressor ammonia, used in Gelita Industry of Brazil, located in the northwest of Parana. We are utilizing the ε-NUT effective methodology for the calculation, the following design parameters and boundary conditions. Was also analyzed the behavior of fluids, water and oil through computational fluid dynamics (CFD) using commercial software ANSYS CFX 14.5 - The results were compared with appropriate empirical correlations. Also in CFD analysis, the predictions of two classical turbulence models (k-ε and Shear Stress Transport) were compared. The ε-NUT analysis pointed to a low effectiveness of shell and tube heat exchanger (a pass in the shell and four in the tubes), not meeting the requirements for the purchase of equipment. These results indicated the bad design of the same, as the number of passes the upper tubes recommended by the TEMA (Tubular Exchanger Manufacturers Association, Inc.) and divergence in the data in project parameters with the calculated real. In the CFD analysis estimated the pressure drop across the shell and the tubes, in addition to convective heat transfer coefficients and from them, the overall heat transfer coefficient. The results were compared with empirical correlations (Bell-Delaware and Petukhov) were satisfactory for the side of the tubes, but for the shell side gave a high deviation. The complexity of the geometry, to the side of the shell, did not allow further refinement of the mesh the computational resource used which can cause errors on a large scale. Finally, turbulence models used properly represented in the flow tubes and the hull, verifying the best fit of the k-ε model for estimating the pressure drop and the SST model to estimate the convective thermal exchange coefficients.